Astragaloside IV Protects Heart from Ischemia and Reperfusion Injury via Energy Regulation Mechanisms. (November 2013) - Tu, Lei; Pan, Chun‐Shui; Wei, Xiao‐Hong; Yan, Li; Liu, Yu‐Ying; Fan, Jing‐Yu; Mu, Hong‐Na; Li, Quan; Li, Lin; Zhang, Yu; He, Ke; Mao, Xiao‐Wei; et al.
Abstract: Objective: This study was designed to investigate the protective potential of AS‐IV against ischemia and I/R‐induced myocardial damage, with focusing on possible involvement of energy metabolism modulation in its action and the time phase in which it takes effect. Methods: SD rats were subjected to 30 minutes LADCA occlusion, followed by reperfusion. MBF, myocardial infarct size, and cardiac function were evaluated. Myocardial structure and myocardial apoptosis were assessed by double immunofluorescence staining of F‐actin and TUNEL. Content of ATP, ADP, and AMP in myocardium, cTnI level, expression of ATP5D, P‐MLC2, and apoptosis‐related molecules were determined. Results: Pretreatment with AS‐IV suppressed MBF decrease, myocardial cell apoptosis, and myocardial infarction induced by I/R. Moreover, ischemia and I/R both caused cardiac malfunction, decrease in the ratio of ATP/ADP and ATP/AMP, accompanying with reduction of ATP 5D protein and mRNA, and increase in P‐MLC2 and serum cTnI, all of which were significantly alleviated by pretreatment with AS‐IV, even early in ischemia phase for the insults that were implicated in energy metabolism. Conclusions: AS‐IV prevents I/R‐induced cardiac malfunction, maintains the integrity of myocardial structure through regulating energy metabolism. The beneficial effect of AS‐IV on energy metabolism initiates during the phase of ischemia.